Solubility study of 2,6- dihydroxybenzoic acid in o-xylene, methanol and acetonitrile using HPLC method - Raja Nur Nadhirah, Raja Othman (2012)
The solubility of 2,6-dihydroxybenzoic acid in three different solvent types was determined at temperature 20ºC, 35 ºC, 50 ºC.The solubility is correlates to the strength of solvent solute interaction which is dependent on the solvent properties.The right solvent is select based on the ability to form the hydrogen bond acceptor or donor between 2,6-DHB solute molecule.The objective in this experiment is to develop the solubility measurement technique in 2,6-DHB in different solvent using HPLC method and to find the Van Hoff correlation as a function of solvent type.The solvent under study were methanol,o-xylene and acetonitrile. 0.05M KH2PO4 at ph 3.2 and methanol was used as the mobile phase.2,6DHB acid was detected at 254nm with an UV-DAD detector and the flow rate is 1.0ml/min.RP-C18 was used and performed at ambient temperature.The solubility of the solute in the solvent at specific temperature can be determined by comparing with the standard calibration curve created using HPLC.From the observation during the saturated solution preparation,methanol can make 2,6-DHB more soluble followed by acetonitrile and o-xylene and from the Van Hoff plot shows that methanol and 2, 6-DHB has strong solute-solvent interaction.